مولانامحمد تقی امینی (1926ء-1991ء) اورعصرحاضرمیں اجتہاد: Maulana Muhammad Taqi Amini (1926-1991) and Ijtihad in the present age - Dr. Haq Nawaz; Ameer Maviya; Muhammad Amir Dehelvi (Al Manhal Research Journal, 2023)
Maulana Taqi Amini presented innovative trends to answer the challenges faced by Muslims, his special topic was jurisprudence debates. He wrote many books on the subject of Islamic jurisprudence and ijtihad. According to Maulana, the need for ijtihad has been there in every era, but the scope of ijtihad has become very wide in the present era. Maulana emphasizes that the ijtihad in the present era should be in accordance with the opinions of the previous jurists, the ijtihad should be of the Shurai style and should be for the purpose of following the rules of Sharia. In this Ijtihad, consideration has been given to changes in circumstances and times. In practice, two types of ijtihad are possible: ijtihad in principles and ijtihad in rulings, which are derived in the light of principles. According to Maulana, there is no need for ijtihad in principles in this age, but ijtihad in rulings is a great need of the time.Not every person has the ability of ijtihad. Mujtahid must have two skills in particular. He should be aware of the objectives of the Shari'ah and be able to reason based on the occasion. Maulana has defined this as knowledge and wisdom. In the same way, the other conditions that the ancient mujtahids set for the mujtahid. Maulana declares all these conditions necessary for the contemporary mujtahid۔Maulana does not like to be confined to a particular jurisprudence. Rather, according to him, speculation should be made by keeping an eye on the entire jurisprudential collection.